Enhancement of tristable energy harvesting using stochastic resonance. (27th December 2018) - Jin, Yanfei; Xiao, Shaoming; Zhang, Yanxia
Abstract: In this paper, stochastic resonance (SR) is exploited within a tristable electromechanical coupled system to enhance energy harvesting. Assuming that the effective capacitance of the piezoelectric element can be neglected, the coupled electromechanical equations are converted to a second-order stochastic differential equation. Using the adiabatic approximation and the linear response theory, the spectral amplification of the equivalent tristable mechanical system is obtained to characterize the SR. It is observed that the spectral amplification exhibits a maximum as a function of the nonlinear stiffness coefficients and noise intensity. That is, both parameter-optimized SR and traditional SR are found in this system, which can be used to amplify the amplitude of the system response and enhance the performance of nonlinear vibration energy harvesting. Moreover, the efficiency in power conversion and the RMS voltage obtained under the SR effect are much higher than those harvested under ambient random vibration alone. The theoretical results are well verified through the numerical simulations of the original electromechanical coupled system.